2023
DOI: 10.1111/jan.15641
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the advance care planning practice preference scale for clinical nurses

Abstract: Aims:The aim of this study was to develop the advance care planning (ACP) practice preference scale and validate its psychometric properties among clinical nurses.Design: An instrument development and validation study was completed in the following three phases: (a) the generation and revision of the item, (b) the preliminary exploration and evaluation of the item and (c) the psychometric evaluation of the scale. Methods:A literature review was conducted to develop the indicator system. A total of 360 clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The Evidence‐based Nursing Practice Competence Scale (EBNPCS) was used to measure the EBNP competence of nurses with EBNP training experience. This Chinese instrument was developed and validated by Wang et al in 2017 (Wang et al, 2017). It can be used for different types of nursing roles.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Evidence‐based Nursing Practice Competence Scale (EBNPCS) was used to measure the EBNP competence of nurses with EBNP training experience. This Chinese instrument was developed and validated by Wang et al in 2017 (Wang et al, 2017). It can be used for different types of nursing roles.…”
Section: Methodsmentioning
confidence: 99%
“…A larger score suggests that the participant is equipped with a higher level of EBNP competence. Prior validation results showed that the EBNPCS has high reliability and validity (Wang et al, 2017). The scale‐level content validity index (S‐CVI) was 0.987.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Uncertainty about advance care planning readiness could hamper efforts to carry out an exercise of advance care planning. 11 A systematic review demonstrated that enhancing the readiness for advance care planning would help patients engage in advance care planning and attenuate the obstacles involved in the process of such planning. 10…”
Section: Advance Care Planning Readinessmentioning
confidence: 99%
“…The Advance Care Planning Readiness Scale (ACPRS‐C) was specifically designed to measure the ACP readiness among patients with chronic disease in China (Wang & Sheng, 2022). The overall Cronbach's alpha coefficient was 0.923, and scale content validity index (S‐CVI) was 0.986 (Wang & Sheng, 2019). The ACPRS‐C has been validated in urban communities and hospitals in the Chinese context, with Cronbach's alpha coefficient between 0.912 and 0.928 (Han, 2022; Yuan & Liu, 2020).…”
Section: Introductionmentioning
confidence: 99%